The Influence of Career Opportunity and Job Involvement on the Performance of Officers at Bank Muamalat KC Semarang Raya - Heni Enawati; Chalimah, Chalimah (Sean Institute, 2025)
This study aims to analyze the influence of career opportunity and job involvement on employee performance at Bank Muamalat KC Semarang Raya. The sample consisted of 41 employees selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire distributed via Google Forms and analyzed using multiple linear regression with SmartPLS version 4.0. The results show that career opportunity has a positive but not significant effect on employee performance, while job involvement has a positive and significant effect. Simultaneously, career opportunities and job involvement have a significant influence on employee performance. Based on the coefficient of determination test, 58% of the variation in employee performance can be explained by the two independent variables, while the remaining 42% is influenced by other factors not examined in this study. These findings indicate that job involvement is a key factor that directly drives performance improvement. Meanwhile, the perception of career opportunities does not yet have a significant impact, suggesting a need to reassess the effectiveness of the organization’s career development system.